2017
DOI: 10.1007/s00262-017-1962-6
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab treatment for immune checkpoint inhibitor-induced enterocolitis

Abstract: Immune checkpoint inhibitors (ICPI), such as ipilimumab [anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4) antibody] and nivolumab or pembrolizumab [anti-programmed cell death protein-1 (PD-1) antibodies], improve survival in several cancer types. Since inhibition of CTLA-4 or PD-1 leads to non-selective activation of the immune system, immune-related adverse events (irAEs) are frequent. Enterocolitis is a common irAE, currently managed with corticosteroids and, if necessary, anti-tumor necrosis factor-α therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(167 citation statements)
references
References 55 publications
2
156
1
4
Order By: Relevance
“…A single dose of infliximab is often sufficient to improve symptoms, although a second infusion 2 weeks later may be needed in some cases 23 25 29 33 49 50. Vedolizumab, a monoclonal antibody blocking α₄β₇ integrin, was administered to six patients with steroid-dependent or steroid-refractory enterocolitis due to ipilimumab 51. Time to steroid-free remission was 56 days, which is comparable to the time to spontaneous remission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single dose of infliximab is often sufficient to improve symptoms, although a second infusion 2 weeks later may be needed in some cases 23 25 29 33 49 50. Vedolizumab, a monoclonal antibody blocking α₄β₇ integrin, was administered to six patients with steroid-dependent or steroid-refractory enterocolitis due to ipilimumab 51. Time to steroid-free remission was 56 days, which is comparable to the time to spontaneous remission.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients with steroid-refractory colitis improved with infliximab, but data are scarce 59 63 72. Patients with anti-PD-1-induced GI IrAE have received mesalazine, vedolizumab,51 tocilizumab and adalimumab-methotrexate combination with reported improvement 73–75. One patient who had skin and GI irAE induced by pembrolizumab improved with secukinumab but subsequently lost antitumour efficacy 76…”
Section: Resultsmentioning
confidence: 99%
“…There are two primary patterns of colitis reported: similar significant ulcerations or normal mucosa with microscopic damage . Management of CPI‐related GEC relies on high‐dose corticosteroids with escalation to infliximab, though alternative second‐line therapies are emerging . The particular steroid administered does not seem to impact clinical course .…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports suggest that vedolizumab may be an effective drug in steroid-refractory or steroid-dependent patients [24, 25]. A recent study with seven patients with mild to moderate, steroid-dependent or steroid-refractory ipilimumab-induced enterocolitis has revealed that six out of seven patients treated with vedolizumab achieve remission and no adverse events were reported [26]. Neither corticosteroids nor infliximab appear to influence response and survival of patients treated with ICPIs [1].…”
Section: Managementmentioning
confidence: 99%